Effects of single and repeated shock wave application on the osteogenic differentiation potential of human primary mesenchymal stromal cells and the osteoblastic cell line MG63 in vitro - Haddouti, El-Mustapha; Reinhardt, Nina; Ossendorff, Robert; Burger, Christof; Wirtz, Dieter C.; de la Fuente, Matias; Schildberg, Frank A. (Frontiers in Bioengineering and Biotechnology, 2023)
Extracorporeal shock wave therapy (ESWT) is a non-invasive and effective option for various musculoskeletal disorders. Recent literature indicates that the parameters for ESWT, such as the optimal intensity, treatment frequency and localization, are still to be determined. Reported studies on the effects of shock wave application (SWA) on primary mesenchymal stromal cells (MSCs) as well as osteoblastic cell lines in vitro are barely available and not standardized. In this study, we designed a special setup to precisely expose primary MSCs and the osteoblastic cell line MG63 to shock waves and subsequently analyzed the resulting cellular responses using standardized protocols to investigate their viability, proliferation behavior, cytokine secretion, and their osteogenic differentiation potential in vitro. The shock wave transducer was coupled to a specifically designed water bath containing a 5 mL tube holder. Primary human MSCs and MG63 cells were trypsinated and centrifuged in a 5 mL tube and exposed to single and repeated SWA using different intensities and number of pulses. Single treatment of MSCs using the intensities 5, 10, 15, 20 and the pulse numbers 100, 250, 500, 750, 1000 at constant pulse repetition frequency of 1 Hz resulted in decreased viability and proliferation of both cell types with increasing intensity and number of pulses compared to controls. No significant difference of the osteogenic differentiation was observed at different time intervals in both cell types when single SWAs were applied. However, repeated SWA over three consecutive days of primary MSCs using low intensity levels 0.1 and 1 showed significant osteogenic differentiation of 4-fold higher of the extracted Alzarin Red S at day 14, whereas MG63 cells showed no significant osteogenic differentiation compared to their corresponding controls. More specifically, repeated SWA triggered significant downregulation of COL1A1, upregulation of RUNX2 and sustained increase of OCN in primary MSCs but not in the cell line MG63 when induced towards the osteogenic differentiation. The effects of SWA on MSCs make it an effective therapy in regenerative medicine. We established a protocol to analyze a standardized SWA on MSCs and were able to determine conditions that enhance the osteogenic differentiation of MSCs in vitro.